PENERAPAN ARTIFICIAL NEURAL NETWORK UNTUK MENDUGA PROGRAM STUDI DI UNIVERSITAS UDAYANA BERDASARKAN NILAI RAPOR - PUTRA, I PUTU BAYU SULAKSANA; KENCANA, I PUTU EKA N.; HARINI, LUH PUTU IDA (E-Jurnal Matematika, 2023)
This research aims to develop an artificial neural network-based estimation system to predict the suitable study program at Udayana University for high school students in Denpasar City based on their report cards. The research is divided into four stages: system overview, user interface design, implementation of the artificial neural network in the system, and system testing. System testing results on report card data for science and social science classes demonstrate that the developed model has good accuracy with an error rate below 7%.